Pengembangan E-Modul Berbasis Model Realistich Mathematics Education (RME) Menggunakan Rumah Adat Bubungan Lima untuk Meningkatkan Pemahaman Konsep pada Materi Bangun Datar Kelas IV Sekolah Dasar - Linda Nirmala; Agus Susanta; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
This study aims to determine the feasibility of the material, language, design, student response, and the effectiveness of the product resulting from the development of an RME-based e-module using the Bubungan Lima traditional house to improve understanding of concepts in elementary school mathematics learning. This research is a Research and Development (R&D) study. The model used in development is the ADDIE model. The subjects in the study were students of SDN 82 Bengkulu City, totaling 22 students in class IV D as the control class, and 22 students in class IV B as the experimental class. The instruments used in this study were interview guides, questionnaires, and conceptual understanding tests in the form of essay questions through pretest and posttest. To measure the effectiveness of conceptual understanding, tests were carried out before and after learning took place in the experimental class and the control class. The data analysis technique in this study was validation analysis using Aiken's V, Interrater Reliability, student responses, and t-test. From the research results it is known that the results of material, language, and design validation, as well as teacher and student responses to e-modules are very feasible and well used in learning. The result of the Significance value is 0.00 which is smaller than Î± = 0.05. Based on the gain-score test from the use of the e-module, it gives a moderate gain score of 48%. So that the understanding of the mathematical concepts of students who use e-modules based on the RME model using the Bubungan Lima traditional house is higher than students who only use textbooks from school so that it is declared effective.